Electronic and optical behaviour of lanthanum doped CaTiO3 perovskite. (20th January 2020) - Rizwan, Muhammad; Usman, Zahid; Shakil, Muhammad; Gillani, S S A; Azeem, S; Jin, H B; Cao, C B; Mehmood, Rana Farhat; Nabi, Ghulam; Asghar, Muhammad Adnan
Abstract: To improve the efficiency of perovskite based solar cells, doping of heavier elements in Perovskite materials (ABX3 ) can modulate its electronic and optical properties significantly. Thus it is important to understand the possible microscopic origin of the band gap modification and optical enhancement after heavier element doping using first-principles studies. Here we investigate the effect of La doping, while substituting the Ca atom, on the electronic and optical properties in CaTiO3 perovskite material using generalized gradient approximation within density functional theory. We observe a decrease in lattice constants and bond lengths in Lax Ca1−x TiO3, mainly due to re-distribution of electronic charge density between La and Oxygen, as confirmed by charge density contour. We further notice a widening of electronic band gap and an upward shift of Fermi level into the conduction band, thus characterizing Lax Ca1−x TiO3 as an n-type material. DOS diagram attributes this shift mainly due to the appearance of La p-DOS and d-DOS and their repulsion with N p-DOS, when La enters into the host lattice at Ca site. Investigation of optical properties upon La Doping in CaTiO3 exhibits further shifting of polarization and refractive index to lower values as compared to its pure counterpart, due to dominating semiconducting behavior and hence one observes a blue shift in absorption and reflection spectrum accordingly. Energy loss function is found to be consistent with absorption and extinction coefficient measured in case of Lax Ca1−x TiO3 . All these results are found to be consistent with the existing experimental and first-principles studies.